The Interleukin-6 Gene Promoter Polymorphism -174 and Atherosclerotic Events in Overweight Transplanted Patients - Jamal Bamoulid; Cécile Courivaud; Marina Deschamps; Béatrice Gaugler; Pierre Tiberghien; Jean-Marc Chalopin; Philippe Saas; Didier Ducloux (Journal of Transplantation)
Chronic inflammation plays a pivotal role in atherosclerosis. We hypothesized that combining overweight and a greater genetic capacity to produce IL-6 predicted by IL-6 gene promoter polymorphism at position -174 (G→C) may allow to identify individuals exhibiting higher IL-6 and C-reactive protein (CRP) concentrations with a higher risk of atherosclerotic events (AE). The occurrence of AE was analyzed with respect to body mass index, IL-6 gene promoter polymorphism at position -174 (G→C), and other relevant risk factors, retrospectively, in 217 renal transplant recipients and, prospectively, in 132. Circulating IL-6 concentrations were closely related to BMI (r=0.55, P=.0005). In overweight patients, serum IL-6 concentration was found to be significantly lower in C carriers than in GG patients (4.2 [1.0–5.1] versus 7.3 pg/mL [4.4–100]; P=.025). The incidence of AE was higher in overweight GG patients (29.5% versus 10.1%; P=.0003). In multivariate analysis, overweight-GG had an increased risk to develop AE (HR 2.96 [95% CI 1.09–8.04], P=.034 in the retrospective cohort, and HR 2.99 [95% CI 0.92–9.33], P=.069 in the prospective cohort). All these data are consistent with a role for both genetic and environmental determinants of inflammation (white adipose tissue mass) in the development of AE in renal transplanted patients.